Innovation and environmentally sustainable economy: Identifying the best practices developed by multinationals in Brazil. (1st September 2017) - Marcon, Arthur; de Medeiros, Janine Fleith; Ribeiro, José Luis Duarte
Abstract: In view of the constant demand for environmentally sustainable innovations and considering the impact that multinational organizations' activities have to speed up or slow down the sustainable development process both locally and globally, this paper identifies and discusses the best environmentally sustainable innovation practices developed by multinationals operating in Brazil. To identify the best practices, we conducted a content analysis based on secondary data of a sustainability report prepared by Fundação Getúlio Vargas and published by a business magazine that annually appoints companies that stand out for their sustainable management practices. The results found in this study allow us to state that the sampled multinationals have been developing product, process, organizational and marketing innovation practices to balance business interests and environmentally sustainable growth. In short, the findings show that multinationals have developed a broad set of actions that cover most of the practices described in the literature. However, considering the practices observed, we note that those related to process innovation appeared more frequently, followed by activities related to organizational innovation, product innovation and marketing innovation. Such observations may be justified once that the shift from a reactive environmental behavior towards a proactive managerial posture involves evolutionary stages. Finally, this paper provides a synthesis of the product, process, organizational and marketing innovations developed by multinationals that may especially benefit researchers and practitioners in search of potential insights towards more sustainable processes, businesses and societies, as well as a framework that describes the transition of multinationals to an environmentally sustainable innovative behavior. Highlights: Innovations implemented by multinationals were mapped and compared to the literature. Product innovations focus mainly on the development of more efficient products. Most process innovation target material savings and process performance. Organizational innovations aim to integrate stakeholders and transfer knowledge. Marketing innovations are implemented through distribution and design modifications.